2015
DOI: 10.1142/s0218810415720211
|View full text |Cite
|
Sign up to set email alerts
|

Post Traumatic Avascular Necrosis of the Proximal Carpal Row - A Case Report

Abstract: We report a case of avascular necrosis of the scaphoid, lunate and triquetrum in a young 21-year-old patient, after a purely ligamentous peri-lunate dislocation of the wrist. He presented with a Mayfield III peri-lunate dislocation after a road traffic accident and underwent an open reduction and internal fixation. Post-operatively, the scapho-lunate gap widened after removal of the temporary K-wires, and he gradually developed avascular necrosis of the scaphoid, lunate and triquetrum, and osteoarthritis of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The patients declined further surgeries and chose nonsurgical treatments. [ 1 ] Didden et al . have reported a case of osteonecrosis of the entire proximal carpal row of the wrist, started briefly after intravenous bisphosphonate administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients declined further surgeries and chose nonsurgical treatments. [ 1 ] Didden et al . have reported a case of osteonecrosis of the entire proximal carpal row of the wrist, started briefly after intravenous bisphosphonate administration.…”
Section: Discussionmentioning
confidence: 99%
“…AVN of multiple carpal bones has been mentioned with a history of trauma, metabolic disorder, corticosteroid consumption, rheumatoid disorders, and systemic lupus erythematosus (SLE). [ 1 2 3 4 ] This case report presents a patient with concomitant AVN of the lunate and proximal pole of the scaphoid.…”
Section: Introductionmentioning
confidence: 99%
“…Ligamentous injury surrounding the lunate may cause an acute interruption of vascular supply and compromise intraosseous circulation of the lunate. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Coll reported a case of palmar dislocation of the scaphoid and lunate, which subsequently resulted in lunate avascular necrosis (AVN). 25 Manohara et al described a case of AVN involving the scaphoid, lunate, and triquetrum following an isolated perilunate dislocation (PLD) of the wrist.…”
Section: Ligamentous Injury and Acute Vascular Compromise Of The Lunatementioning
confidence: 99%
“…25 Manohara et al described a case of AVN involving the scaphoid, lunate, and triquetrum following an isolated perilunate dislocation (PLD) of the wrist. 26 Bourne et al reported six individuals with Kienböck disease and a history of scapholunate (SL) dissociation. Five out of the six had a single traumatic event that had occurred between 8 months and 7 years before the onset of Kienböck disease.…”
Section: Ligamentous Injury and Acute Vascular Compromise Of The Lunatementioning
confidence: 99%
“…T here are some reports of avascular necrosis of carpal bones. [1][2][3][4] Risk factors of avascular necrosis of bones have been reported to include corticosteroid use, smoking, gout, alcoholism, infections, storage disorders, marrow-infiltrating diseases, coagulation defects, hemoglobinopathies, fat emboli, liver disease, hyperlipidemia types II and III, hemophilia, rheumatoid arthritis, systemic lupus erythematosus, and pancreatitis. 5 Kienböck's disease and Preiser's disease comprise avascular necrosis of the lunate and scaphoid, respectively.…”
Section: Introductionmentioning
confidence: 99%